Functional outcomes of tendon transfer for brachial plexus birth palsy using the Hoffer technique. (February 2020) - Alluri, Ram K.; Lightdale-Miric, Nina; Meisel, Erin; Kim, Gina; Kaplan, Jesse; Bougioukli, Sofia; Stevanovic, Milan
Abstract : Aims: To describe and analyze the mid-term functional outcomes of a large series of patients who underwent the Hoffer procedure for brachial plexus birth palsy (BPBP). Methods: All patients who underwent the Hoffer procedure with minimum two-year follow-up were retrospectively reviewed. Active shoulder range of movement (ROM), aggregate modified Mallet classification scores, Hospital for Sick Children Active Movement Scale (AMS) scores, and/or Toronto Test Scores were used to assess functional outcomes. Subgroup analysis based on age and level of injury was performed. Risk factors for subsequent humeral derotational osteotomy and other complications were also assessed. A total of 107 patients, average age 3.9 years (1.6 to 13) and 59% female, were included in the study with mean 68 months (24 to 194) follow-up. Results: All patients demonstrated statistically significant improvement in all functional outcomes and active shoulder abduction and external rotation ROM (p < 0.001). Patients < 2.5 years of age had higher postoperative AMS, abduction ROM and strength scores, and aggregate postoperative Toronto scores (p ≤ 0.035) compared to patients ≥ 2.5 years old. There were 17 patients (16%) who required a subsequent humeral derotational osteotomy; lower preoperative AMS external rotation scores and external rotation ROM were predictive risk factors (p ≤ 0.016). Conclusion: Patients with BPBP who underwent the Hoffer procedure demonstrated significant improvement in postoperative ROM, strength, and functional outcome scores at mid-term follow-up. Patients younger than 2.5 years at the time of surgery generally had better functional outcomes. Limited preoperative external rotation strength and ROM were significantly associated with requirement for subsequent humeral derotational osteotomy. In our chort significant improvements in shoulder function were obtained after the Hoffer procedure for BPBP. Cite this article: Bone Joint J 2020;102-B(2):246–253.